2007
DOI: 10.1016/j.reprotox.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal flaxseed diet during pregnancy or lactation increases female rat offspring's susceptibility to carcinogen-induced mammary tumorigenesis

Abstract: Flaxseed contains several dietary components that have been linked to low breast cancer risk; i.e., n-3 polyunsaturated fatty acids (PUFAs), lignans and fiber, but it also contains detectable levels of cadmium, a heavy metal that activates the estrogen receptor (ER). Since estrogenic exposures early in life modify susceptibility to develop breast cancer, we wondered whether maternal dietary intake of 5% or 10% flaxseed during pregnancy or lactation (between postpartum days 5 and 21) might affect 7,12-dimethylb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Another potential explanation for the contradictory finding between these studies is that terminal end bud density at puberty may not be a consistent predictor of mammary tumor risk in rodents as suggested by recent studies (40,41).…”
Section: Discussionmentioning
confidence: 90%
“…Another potential explanation for the contradictory finding between these studies is that terminal end bud density at puberty may not be a consistent predictor of mammary tumor risk in rodents as suggested by recent studies (40,41).…”
Section: Discussionmentioning
confidence: 90%
“…Maternal dietary intake of excess fat or other dietary factors during pregnancy have been shown to affect female offspring's later susceptibility to develop mammary cancer in rats (10)(11)(12). This increase in risk is thought to occur due to an increase in fetal estrogenic environment caused by the maternal diet (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Results from animal studies suggest that maternal dietary or hormonal exposures during pregnancy may have longlasting effects on mammary tumorigenesis among the female offspring (9)(10)(11)(12). For example, maternal exposure to a high-fat diet during pregnancy increases a female offspring's susceptibility to develop carcinogen-induced mammary tumors in rats (9,13), whereas whole wheat flour, containing lignans, and fish oil reduces the risk (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that after the administration of different doses of FEO (10,20,25,40 and 50 g/ml), the oxytocin (0.1, 1 and 10 mU/ml) -and prostaglandin E2 (5 × 10 −5 M) -induced contractions were reduced significantly. The estimated LD 50 was 1326 mg/kg for FEO.…”
Section: Fennel (Foeniculum Vulgare)mentioning
confidence: 99%
“…The maternal dietary intake of 5% or 10% flaxseed during pregnancy or lactation (between postpartum days 5 and 25) might affect 7,12 dimethylbenz[a]anthracene (DMBA)-induced mammary tumorigenesis in the rat offspring. It is proclaimed that both in utero and postnatal 5% and 10% flaxseed exposures can shorten mammary tumor latency, and 10% flaxseed exposure increased tumor multiplicity, compared to the controls [25].…”
Section: Flaxseed (Linum Usitatissimum)mentioning
confidence: 99%